Peningkatan Daya Saing Melalui Manajemen Strategi Fungsional di SMA Bakti Ponorogo - Hakim, Nasron; Bambang Wahrudin (Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan Jawa Timur, 2023)
Educational institutions need strategies that are applicable in developing their institutions, including in the formulation of strategies that must be able to be fully implemented down to the smallest part of the institution. The focus of this research is to identify and discuss some of the basic principles of functional strategy at SMA Bakti Ponorogo which have risen to increase competitiveness in a highly competitive educational environment. This study aims to provide an in-depth analysis of functional strategy, which consists of marketing strategy, financial strategy, production strategy, human resources strategy, and R & D strategy in an effort to increase competitiveness. The method used is descriptive qualitative. The results showed that SMA Bakti Ponorogo has implemented a functional strategy but not yet in depth. Some of the things that have been planned by the manager need to be added to various efforts as theoretical concepts so as to increase competitiveness.